Bio-Waste in Reverse Logistics - Various Size Cities on the Example of South-Eastern Poland - KOC-JURCZYK Justyna; JURCZYK Łukasz; PODOLAK Agnieszka (Architecture, Civil Engineering, Environment)
The circular economy (CE) aims to keep the maximum value of products and materials in a closed loop for longer periods, thus decoupling the use of natural resources from economic growth. Reverse logistics in the management of municipal biowaste falls within the scope of CE activities. This study compares the mass of bio-waste collected separately to the mass forecast at various administrative levels in Poland: country, voivodeship, cities with over 50 thousand inhabitants, and cities under 50 thousand inhabitants. Discrepancies were found between the collected mass of bio-waste and its predicted mass, which may be due to several reasons. Firstly, rural residents often use bio-waste for their own household needs. Additionally, in rural areas, due to the dispersion of buildings, the cost of obtaining the same amount of bio-waste is much higher compared to more urbanized areas. Processing bio-waste into organic fertilizer is a process that meets the assumptions of a circular economy and creates an environmentally friendly product. Unfortunately, in the case of Poland, there is no data on collected bio-waste earlier than 2019. There is also no information on the mass of biologically managed bio-waste at all administrative levels. Therefore, reporting on the management of municipal bio-waste at all administrative levels should be improved. The work also discusses the issue of collection and management of bio-waste, taking into account logistics processes.